Characteristics and Source Apportionment of the Vertical Distribution of Ozone at a Site of the Pearl River Delta Region of China. Issue 6 (23rd June 2021) - Wang, Xinqi; Xiang, Yan; Liu, Wentao; Yun, Long; Lv, Lihui; Zhang, Mingdi; Xu, Junzheng; Fan, Guangqiang; Ou, Jinping; Wang, Qiubu; Duan, Danyang; Zhang, Tianshu
Abstract: Ozone pollution adversely affects human health. In recent years, ozone pollution has become an important research topic and a challenge. By combining differential absorption lidar (DIAL), meteorological gradient tower data, the Weather Research and Forecasting (WRF) model, and the backward trajectories model, changes in vertical ozone concentration, the influencing factors on ozone vertical distribution, and ozone sources were analyzed in Shenzhen from September 20 to 30, 2019. Results indicated that from September 25 to 30, there was obvious residual ozone and transport at night. The analysis of ozone concentration and meteorological factors shows that the temperatures of 291.3–301.8 K and the humidity of 19.4%–71.6% were conducive to ozone formation. As height increased from less than 0.1–0.3 km, the average ozone concentration increased, and the average NO2 concentration decreased. The analysis of potential ozone sources showed that ozone was mainly transported from the northeast of China and that the highest concentration of ozone mainly comes from southeast of Jiangxi province in southeastern China. Key Points: There was obvious residual ozone and transport at night from September 25 to 30 The temperatures of 291.3–301.8 K and the humidity of 19.4%–71.6% were conducive to ozone formation Ozone is mainly transported from the northeast of China